2013
DOI: 10.1002/jpln.201100185
|View full text |Cite
|
Sign up to set email alerts
|

Responses of photosynthesis, chlorophyll fluorescence, and grain yield of maize to controlled‐release urea and irrigation after anthesis

Abstract: Controlled‐release urea (CRU) is a new type of urea, which may increase crop nitrogen (N)‐use efficiency compared with conventional urea (CU), but the conditions where it outperforms urea are not well defined. A field experiment assessing responses of plant growth and grain yield of maize to CRU and irrigation was conducted on a typical agricultural farm in Shandong, China. Five treatments of the two types of urea (75, 150 kg N ha–1, 0 kg N ha–1) were applied as basal fertilizer when sowing maize, and two wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 29 publications
2
24
0
4
Order By: Relevance
“…Shao et al [44] found a significant positive coupling effect between N and water on maize yield. In our study, there were significant interactions between water and CRU on increasing maize yield and improving N utilization rates.…”
Section: Discussionmentioning
confidence: 99%
“…Shao et al [44] found a significant positive coupling effect between N and water on maize yield. In our study, there were significant interactions between water and CRU on increasing maize yield and improving N utilization rates.…”
Section: Discussionmentioning
confidence: 99%
“…and ) were increased depending on CRK application in the boll‐opening and maturing stage. The high chlorophyll concentration and chlorophyll fluorescence parameters allowed the increment in P n with sufficient soil K supply ( Shao et al, ). There was a positive linear correlation between plant‐available K and P n rate for the three K sources (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We propose that increases in chlorophyll content arise from resource conservation and increased internal N utilisation efficiency under ureic N assimilation. Shao et al (2013) demonstrated that net photosynthetic rate, chlorophyll concentration and leaf-area index were increased significantly under controlled-release urea (CRU), compared with conventional urea-treated maize plants at grain filling, and produced a higher yield, although this may simply relate to the higher availability of nitrogen per se with reduced degradation. However, Esteban et al (2016) demonstrated experimentally that the biophysical parameters of the photosynthetic apparatus of urea-grown Medicago trunculata plants displayed a dosedependent improvement in energy conservation, which was higher than that observed in nitrate-and ammonium-treated plants.…”
Section: Increased Photosynthesismentioning
confidence: 99%